EGR1 controls divergent cellular responses of distinctive nucleus pulposus cell types. Issue 1 (December 2016) - van den Akker, Guus; Surtel, Don; Cremers, Andy; Hoes, Martijn; Caron, Marjolein; Richardson, Stephen; Rodrigues-Pinto, Ricardo; van Rhijn, Lodewijk; Hoyland, Judith; Welting, Tim; Voncken, Jan
Abstract Background Immediate early genes (IEGs) encode transcription factors which serve as first line response modules to altered conditions and mediate appropriate cell responses. The immediate early response gene EGR1 is involved in physiological adaptation of numerous different cell types. We have previously shown a role for EGR1 in controlling processes supporting chondrogenic differentiation. We recently established a unique set of phenotypically distinct cell lines from the human nucleus pulposus (NP). Extensive characterization showed that these NP cellular subtypes represented progenitor-like cell types and more functionally mature cells. Methods To further understanding of cellular heterogeneity in the NP, we analyzed the response of these cell subtypes to anabolic and catabolic factors. Here, we test the hypothesis that physiological responses of distinct NP cell types are mediated by EGR1 and reflect specification of cell function using an RNA interference-based experimental approach. Results We show that distinct NP cell types rapidly induce EGR1 exposure to either growth factors or inflammatory cytokines. In addition, we show that mRNA profiles induced in response to anabolic or catabolic conditions are cell type specific: the more mature NP cell type produced a strong and more specialized transcriptional response to IL-1β than the NP progenitor cells and aspects of this response were controlled by EGR1. Conclusions Our current findings provide important substantiation of differential functionality among NP cellular subtypes. Additionally, the data shows that early transcriptional programming initiated by EGR1 is essentially restrained by the cells' epigenome as it was determined during development and differentiation. These studies begin to define functional distinctions among cells of the NP and will ultimately contribute to defining functional phenotypes within the adult intervertebral disc.